Ensino remoto: refletindo os desafios enfrentados na pandemia pelo curso de Letras-Língua e Literatura Japonesa da Universidade Federal do Amazonas - Silva, Ana Cristina Bruce da (Brasil, 2025)
With the Covid-19 pandemic, caused by the new coronavirus (SARS-COV-2), the world has had to adopt restrictive measures, such as remote classes and work. Universities, including the Federal University of Amazonas (UFAM), suspended face-to-face classes and implemented remote teaching, facing challenges such as the lack of internet access, equipment and digital literacy on the part of students and teachers. The research focuses on the Letters - Japanese Language and Literature course at UFAM during the 2020/1 and 2020/2 academic periods, seeking to analyze the adaptation to online classes, the tools used, access to teaching materials and the difficulties faced. The implementation of remote teaching as an emergency solution brought significant challenges for students and teachers, who had to adapt quickly to new methodologies and digital platforms. Although the difficulties were evident, this experience highlighted the relevance of educational technologies and highlighted the inequalities in access to digital resources. To this end, we sought theoretical grounding in Libâneo (2006), who addresses teaching and its interpretations; Kenski (2007), who focuses on teaching and digital technologies; and Granja (2021), highlighting digital teaching materials. As well as presenting documentary and bibliographical information, the study aims to contribute to future research into the teaching and learning of Japanese in Brazil.